Palaeomicrobiology: Application of Ancient DNA Sequencing to Better Understand Bacterial Genome Evolution and Adaptation - Arriola, Luis A.; Cooper, Alan; Weyrich, Laura S. (Frontiers in Ecology and Evolution, 2020)
Next Generation Sequencing (NGS) has unlocked access to the wide range of non-cultivable microorganisms, including those present in the ancient past. The study of microorganisms from ancient sources (palaeomicrobiology) using DNA sequencing now provides a unique opportunity to examine ancient microbial genomic content, explore pathogenicity, and understand microbial evolution in greater detail than ever before. As a result, current studies have focused on reconstructing the evolutionary history of a number of human pathogens involved in ancient and historic pandemic events. These studies have opened the door for a variety of future palaeomicrobiology studies, which can focus on commensal microorganisms, species from non-human hosts, information from host-genomics, and the use of bacteria as proxies for additional information about past human health, behavior, migration, and culture. Here, we describe the origin and the historical and recent advances in the field of palaeomicrobiology, review some of the most notable ancient pathogenic microorganism studies, and provide perspectives on how NGS and whole genome information from ancient microorganisms contribute to our understanding of bacterial evolution on a broader scale. We conclude by exploring the application of newly developed tools in palaeomicrobiology and discussing how future studies can improve our current understanding of the co-evolution relationships between humans and non-pathogenic microbes.